The factors of students’ involvement on student-centered learning method - Duratul Ain Tholibon; Masyitah Md Nujid; Hamizah Mokhtar; Jamilah Abd Rahim; Siti Safirah Rashid; Azlinda Saadon; Dulina Tholibon; Rudi Salam (Institute of Advanced Engineering and Science, 2022)
Student-centered learning (SCL) is one of the teaching methods commonly used nowadays as it encourages the active participation and engagement of students in the classroom, especially for the engineering theoretical subject. This study is aimed to examine the factors of students’ involvement and participation towards the SCL Teaching Method in terms of the activities, benefits, problems, and limitations of student involvement. The quantitative data are obtained from the responses of students that enroll in an engineering theoretical subject in the Universiti Teknologi MARA (UiTM) Pahang Civil Engineering Diploma Program. These questionnaires were being classified into five major factors that are the formation of group studies for SCL activities, activities conducted for SCL teaching method, benefits that they gain from SCL method, problems that they encounter during SCL, and suggestions for student improvement towards the activity SCL session. The collected data were analyzed quantitatively by using the percentage and mean method in SPSS computer software. The Relative Importance Index (RII) system was used to quantify the relative importance of involvement factors. This study revealed three main factors affecting the participation and engagement of students in the classroom. This study has an important contribution to help academicians to improve and enhance their teaching method to achieve the objective of the SCL method in the future.